THE IMPACTS OF STEM SUPPORTED SCIENCE TEACHING ON 8TH GRADE STUDENTS’ ELIMINATION OF MISCONCEPTIONS ABOUT "SOLID, FLUID AND GAS PRESSURE", AND THEIR ATTITUDES TOWARDS SCIENCE AND STEM - Benli Ozdemir, Esra (International Online Journal of Education and Teaching, 2020)
In the study, it was aimed to determine the misconceptions of 8th grade students about the concepts of "solid, fluid and gas pressure", to correct these misconceptions by using STEM supported Science activities, and to improve their attitudes towards Science and STEM. The study group consisted of 46 8th grade students at a public school in Ankara in the fall semester of the 2019-2020 school year. They were determined using the appropriate sampling method, one of the non-probabilistic sampling methods In the study, experimental method with pre-test-post-test single group model was used. The study was conducted with two experimental groups in order to increase the reliability of the research. The data were collected via the "Pressure Conceptual Understanding Test", “Attitude Scales towards Science and STEM”. The results revealed that the students had misconceptions about “Pressure" in the pre-test. It was also found out that STEM was useful to overcome the detected misconceptions, largely overcome the misconceptions existing in students, and the participant students’ attitudes towards STEM developed at a positive level, whereas there was no change in their attitude towards Science.